A 126 μW readout circuit in 65nm CMOS with successive approximation based thresholding for domain wall magnet based random number generator - Narasimman, Govind (2020)
We present a novel readout circuit for a ferromagnetic Hall cross-bar based random number generator. The random orientation of magnetic domains are result of anomalous Hall-effect. These ferromagnetic Hall cross-bar structures can be integrated with the read out circuit to form a plug and play random number generator. The system can resolve up to 15-20 μV Hall-voltages from Hall probe. Application of current densities around 10 12 A/m 2 through the Ferromagnetic Hall cross-bar produces random Hall-voltage on the output terminals. To amplify the weak Hall-voltages (10-100 μV) in the presence of DC offsets, a modulation scheme is used to up-convert the signal and a band-pass amplifier is used to amplify the modulated signal. The bandpass amplifier circuit, motivated by neural recording amplifier is designed in 65nm CMOS and consumes 126 μW of power from a 1.2 V supply. Further, we present a successive approximation algorithm and its embedded implementation to set the desired threshold for digitizing the amplified Hall-voltage in presence of signal drift. Experimental results show that the resulting system can tolerate drifts in voltage up to 440 μV.